People’s perception and awareness on air pollution in rural and urban areas of Mymensingh Sadar upazila - Sarker, R; Yeasmin, M; Rahman, MA; Islam, MA (Progressive Agriculture, 2018)
The present study was conducted to investigate peoples’ perception level and awareness of air pollution in some selected areas of Mymensingh sadar upazila. The relationship of independent variables (age, educational qualification, family size, residence and communication exposure) with the peoples’ perception level and awareness of air pollution (dependent variable) was done to understand the objectives of the study. Six Hundreds (600) respondents were selected randomly from six study sites under Mymensingh sadar upazila for collecting data during the period of Jan 2016-April, 2017. Pearson’s product-moment correlation coefficients were computed to examine the relationship between the concerned variables. The findings revealed that about half (46.67 percent) of the peoples had medium perception and awareness, 31.67 percent had low and 21.67 percent had high perception and awareness about air pollution. In rural areas, 43.33 percent respondents had low, 50.00 percent had medium and only 6.67 percent had high perception and awareness of air pollution. In urban areas, 20.00 percent respondents had low, 43.33 percent had medium and 36.67 percent had high perception and awareness of air pollution. Majority of the respondents (93.33 percent) were lacking of proper awareness of air pollution in rural areas while 63.33 percent in urban areas. Out of five independent variables, three variables such as educational qualification, residence and communication exposure had positive and significant relationship, age had negative and significant relationship and family size had no relationship with their perception and awareness of air pollution. Progressive Agriculture 29 (1): 22-32, 2018